Dynamic Mathematical Models' System and Synchronization. (19th November 2021) - Alazzam, Malik Bader; Hamad, Abdulsattar Abdullah; AlGhamdi, Ahmed S
Abstract : We created the equilibrium, which includes sickness outcomes, health and risk behaviors, environmental factors, and health-related assets and delivery systems, and it should be incorporated in system Dyc (dynamic) modelling of chronic disease prevention. System Dyc has the ability to model a variety of interconnected illnesses and dangers, as well as the interaction between delivery systems and afflicted people, as well as state and national policies. This paper proposes a unique idea. Hybrid synchronization utilizes four positive LYP (Lyapunov) exponents based on state feedback management with two identical systems of the Lorenz system 6D HYCH system.